2000
DOI: 10.1038/sj.bjp.0703515
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate and sphingosylphosphorylcholine constrict renal and mesenteric microvessels in vitro

Abstract: 1 Sphingolipids such as sphingosine-1-phosphate (SPP) and sphingosylphosphorylcholine (SPPC) can act both intracellularly and at G-protein-coupled receptors, some of which were cloned and designated as Edg-receptors. 2 Sphingolipid-induced vascular e ects were determined in isolated rat mesenteric and intrarenal microvessels. Additionally, sphingolipid-induced elevations in intracellular Ca 2+ concentration were measured in cultured rat aortic smooth muscle cells. 3 SPPC and SPP (0.1 ± 100 mmol l 71 ) caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 35 publications
3
114
0
Order By: Relevance
“…59 S1P also induces pertussis toxin-sensitive transient calcium mobilization in cultured smooth muscle cells derived from rat aorta. 69 Thus, S1P appears to modulate calcium-mobilizing pathways in smooth muscle cells in a manner similar to other classical G-protein-coupled receptor agonists.…”
Section: Vasoconstriction Pathways Elicited By Sphingosine-1-phosphatmentioning
confidence: 99%
“…59 S1P also induces pertussis toxin-sensitive transient calcium mobilization in cultured smooth muscle cells derived from rat aorta. 69 Thus, S1P appears to modulate calcium-mobilizing pathways in smooth muscle cells in a manner similar to other classical G-protein-coupled receptor agonists.…”
Section: Vasoconstriction Pathways Elicited By Sphingosine-1-phosphatmentioning
confidence: 99%
“…The actions of many G-protein coupled receptors are mediated by release of PLC-dependent IP 3 -gated Ca 2+ from the ER (Fukata et al, 2001). S1P receptors also have a role in mobilization of intracellular Ca 2+ in various cell types (Bischoff et al, 2000;Spiegel and Merrill, 1996;Young and Nahorski, 2002). The pacemaking mechanisms of intestinal ICC are driven by activation of Ca 2+ -dependent pacemaker channels, such as TRP or Ca 2+ -activated Cl -channels, which are coupled with release of IP 3 -gated Ca 2+ from the endoplasmic reticulum (Huizinga et al, 2002;Kim et al, 2005;Nakayama et al, 2007;Ward et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that both PAF and ceramides may result in transformation of VSM cells from one phenotype to another, as is typical in the atherosclerotic process [53,54,72,73]. In addition, like we see in MgD, PAF produces vasoconstriction of blood vessels and a variety of VSM types [for recent review, see 69], as do several of the ceramides [69,74,75]. A number of investigators employing intravital microscopy techniques, similar to those used by our laboratories [76][77][78][79][80], have demonstrated that PAF increased the number of white blood cells in the microvessels concomitant with intense vasoconstriction-spasms with increasing concentrations of the putative lipid mediator (i.e., PAF), less leukocyte rolling, and increased adherence of the leukocytes to the endothelial surfaces with increases in vascular-capillary permeability [78][79][80].…”
Section: Is the Mysterious Intermediary Molecule Possibly Related To mentioning
confidence: 99%